ANALISIS PROSES PENGEMBANGAN PRODUK BARU DALAM RANGKA MENGHADAPI PERSAINGAN BISNIS (Kasus Pada MM. Cake & Bakery Pekanbaru) - Alkurni, Wais; Zuliarni, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
New product development should be the center of attention for the company as a clear contribution to the survival and prosperity of the company. In addition, new product development is closely associated with the success of a company in an effort to increase sales. By doing new product development, the company the opportunity to get new customers will be even greater. If the customer increases, then sales will increase. Of course, if the products are sold in accordance with what the expectations of consumers.The purpose of this study is to investigate and explain the new product development process undertaken MM. Cake & Bakery in order to face competition.The problem faced by MM. Cake & Bakery to market the resulting product is a consumer appetite is likely to change, more and more variety of products and new products on the market. For the MM. Cake & Bakery should be able to anticipate this situation, if the MM. Cake & Bakery is less sensitive to these conditions will lead to less influence on the products produced and marketed. Another issue that is important is the proliferation of businesses that target the same market, so it is necessary for MM. Cake & Bakery to develop products according to the needs and tastes of consumers.In general, the stages of new product development process includes eight stages: idea creation, idea screening, concept development and testing, marketing strategy, business analysis, product development, test marketing and commercialization.The method in this research include new product development process is carried out by MM. Cake & Bakery, the source of the data used are primary data, the data is in the form of interviews through focus group discussions with informants who are considered competent in answering questions and secondary data, the data is in the form of the data obtained and collected from MM. Cake & Bakery Jl. Kulim No. 61 C, Pekanbaru contains information relating to this research, such as company profile, targets and actual sales, the list of products along with the unit price and other data relevant to the study.Jom FISIP Volume 1 No.2 Oktober 2014 Page 2The results showed that the stages of new product development process is carried out MM. Cake & Bakery Pekanbaru there are six stages: idea creation, idea screening, concept development and testing, marketing strategy, business analysis and commercialization.In the implementation of new product development, MM. Cake & Bakery modifying existing products or changes, be it of the characteristics of the products, increase product quality, increase product type, product taste and change the shape and size of the product.Keywords: marketing strategy, new product, new product development process.